The colpocitograma in threatened abortion - Mongrut Steane, Andrés (2015)
The author have studied the eosinophilic index in colpocytogram of 60 women with the diagnosis of threatened abortion; they state there is a negative correlation between the % of eosinophilic cells and the prognosis of the pregnancy. The higher the index, lower the chances to end successfully the pregnancy. They remark, the simplicity of the method for the evaluation of each particular case.